Generic Benchmarking in the aim of Improving Clusters’ Performances in Serbia - Krstić, Bojan D; Stanisavljevic, Nevena; Stanisic, Tanja (Industrija, 2014)
By the generic benchmarking, cluster organizations can reduce risk, and allow better use of own development potentials. The purpose of this paper is to establish a methodological framework for benchmarking of cluster organizations in Serbia. The examination of the formation, functioning and development process of cluster organizations, as well as the existing benchmarking methodologies in European clusters, were used to set up a customized methodological framework for benchmarking in this paper. The applicability of the recommended methodology is verified by the realisation of a comparative study between two cluster organizations in Serbia. The result of this benchmarking of clusters’ performances represents, among others, determined set of measures and actions to improve the business performances of the Medical Start up Cluster. The research is useful not only to creators of regional development policies, providing a useful benchmarking methodology, but also to the management of cluster organizations in Serbia, which receive a tool which continuous application may allow improving the performances of cluster members and cluster organizations as a whole.